2015
DOI: 10.1016/j.ijpharm.2015.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of amorphous furosemide increases the oral drug bioavailability in rats

Abstract: A glass solution of the amorphous sodium salt of furosemide (ASSF) and polyvinylpyrrolidone (PVP) (80:20 w/w%) was prepared by spray drying. It was investigated if PVP was able to stabilise ASSF during storage and dissolution and whether this influenced the in vivo performance of the glass solution after oral dosing to rats. The glass solution had a glass transition temperature of 121.3±0.5°C, which was significantly higher than that of the pure drug (101.2°C). ASSF in the glass solution was stable for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The control group received FSP (prepared in 0.5% sodium carboxymethyl cellulose), while the test group was treated by FSLN at a dosing rate of 15 mg kg À1 . 27 The blood samples were collected in centrifuge tubes containing K 2 EDTA (1.8 mg mL À1 , NOVAC POLYMED, supplied by Poly Medicure Ltd., Faridabad, India), from the retro-orbital plexus using heparinized glass capillary tubes at different time points (0, 0.25, 0.5, 1.5, 2, 3, 6, 9, 12 and 24 h) aer dosing. The blood samples were centrifuged at 3000 rpm for 15 min to separate the plasma.…”
Section: Methodsmentioning
confidence: 99%
“…The control group received FSP (prepared in 0.5% sodium carboxymethyl cellulose), while the test group was treated by FSLN at a dosing rate of 15 mg kg À1 . 27 The blood samples were collected in centrifuge tubes containing K 2 EDTA (1.8 mg mL À1 , NOVAC POLYMED, supplied by Poly Medicure Ltd., Faridabad, India), from the retro-orbital plexus using heparinized glass capillary tubes at different time points (0, 0.25, 0.5, 1.5, 2, 3, 6, 9, 12 and 24 h) aer dosing. The blood samples were centrifuged at 3000 rpm for 15 min to separate the plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Nielsen et al have shown that the glass solution of the amorphous sodium salt of furosemide with PVP has shown good stability and also better oral bioavailability in rats compared with pure furosemide. The stabilizing effect of PVP on furosemide led to the enhanced relative oral bioavailability of up to 263% in rats compared with pure furosemide [ 161 ]. PVP also stabilizes several active substances in different dosage forms e.g., nitroglycerine, isosorbide dinitrate, ascorbic acid, interferon, iodine, theophylline, etc [ 3 ].…”
Section: Pharmaceutical and Other Applicationsmentioning
confidence: 99%
“…Using an amorphous form of the drug is an excellent option to improve low aqueous solubility, since both the dissolution rates as well as the apparent solubility are enhanced when converting a crystalline form to its amorphous counterpart [ 5 ]. However, a major challenge with the use of amorphous drugs is their low physical stability, that is, their tendency to recrystallize upon formulation, storage, or administration [ 6 ]. This has led to an urgent need to increase the understanding of the link between the physicochemical properties of an amorphous drug and potential interactions with common excipients on the overall physical stability of amorphous forms.…”
Section: Introductionmentioning
confidence: 99%